Integrating Gamification and SEL to Strengthen Elementary Students’ Character in Indonesia - Ali Ridho; Alfiansyah Alfiansyah; Irma safitri; Rohaili Rohaili (LP2M IAI AL-KHAIRAT PAMEKASSAN, 2025)
Gamification and SEL (Social Emotional Learning) have become effective strategies in strengthening children's character through the active role of teachers and continuous school support. This study explores the role of teachers and school support in implementing gamification and SEL as strategies to strengthen student character at the elementary education level in Indonesia. The research was conducted qualitatively by collecting data through semi-structured interviews, classroom observations, and document analysis involving several teachers and students engaged in innovative learning practices. The study indicates that teacher competencies, including the ability to adapt the curriculum, implement various learning strategies, and establish effective communication, are considered crucial factors in the application of gamification and SEL in classrooms. Teachers who receive practical and continuous training tend to be more confident and successful in managing game-based learning and developing students' social-emotional skills. Moreover, institutional support through clear school policies and active parental involvement has been shown to contribute positively to learning outcomes. This research emphasizes the importance of collaboration between teachers, schools, and the community in creating a dynamic and inclusive learning environment that not only promotes academic achievement but also shapes resilient and adaptive student character. The findings of this study are expected to serve as a reference in formulating policies that support educational innovation in Indonesia.